1961
DOI: 10.1039/jr9610004235
|View full text |Cite
|
Sign up to set email alerts
|

825. Transamination. Part II. The non-enzymic reactions between pyridoxamine and pyruvic acid and between pyridoxal and alanine

Abstract: The reaction between pyridoxamine and pyruvic acid in water a t 25" over the range pH 7-10 yields pyridoxal and alanine. Kinetic and spectroscopic studies show that the reaction proceeds by the fast and reversible formation of the Schiff's base. The rate-limiting step, which is general-acid catalysed, is the interconversion of this and the isomeric Schiff's base, i.e., the change *CH=N.CHMeCO,H *CH,*N=CMe*CO,H. The reverse reaction (formation of pyridoxamine and pyruvic acid) has also been studied, but in less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

1968
1968
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 0 publications
2
26
0
Order By: Relevance
“…In addition, formation constants of ketimines of pyrldoxamine and pyruvate have been determined spectrophotometrlcally as a function of pH. These experimental values agreed with predicted formation constants calculated from pK'^ values of the dissociable ketimines and reactants (Banks _et , 1961).…”
Section: Equilibrium Constants For Formation Of Imlnessupporting
confidence: 65%
See 3 more Smart Citations
“…In addition, formation constants of ketimines of pyrldoxamine and pyruvate have been determined spectrophotometrlcally as a function of pH. These experimental values agreed with predicted formation constants calculated from pK'^ values of the dissociable ketimines and reactants (Banks _et , 1961).…”
Section: Equilibrium Constants For Formation Of Imlnessupporting
confidence: 65%
“…A similar equation was derived for measuring apparent equilibrium constants for ketimine formation from pyridoxamine and pyruvate (Banks et al, 1961). Consider the above reaction where A is now keto acid, P = pyridoxamine, I = ketimine.…”
Section: Spectral Methods For Determining Imlne Formation Constantsmentioning
confidence: 99%
See 2 more Smart Citations
“…As the production ofextramitochondrial acetyl-CoA for fatty acid biosynthesis from either acetate or carbohydrate involves the action of acetyl-CoA synthetase (EC 6.2.1.1) or ATP citrate lyase (EC 4.1.3.8) respectively (Kornacker & Lowenstein, 1965), the activities of these enzymes have been measured in the liver, kidney cortex and perirenal adipose tissues ofthe lamb at three stages ofdevelopment: 140 days' gestational age and 1 day and 7 days after birth. Banks, Diamantis & Vernon (1961) found that the rate of transamination between pyridoxal and amino acids increased with buffer concentration; Bruice & Topping (1963a,b) showed that there was general acid-and base-catalysed transamination between amino and oxo acids. They suggested that the base removed the proton shown in the structure C=-N-C-H of the intermediate aldimine (cf. /\ Braunstein & Shemyakin, 1953;Metzler, Ikawa & Snell, 1954).…”
Section: A L Sepherd (Department Of Phy8iology Andmentioning
confidence: 99%